2020
DOI: 10.1093/mnras/staa3289
|View full text |Cite
|
Sign up to set email alerts
|

Stellar velocity dispersion and dynamical mass of the ultra diffuse galaxy NGC 5846_UDG1 from the keck cosmic web imager

Abstract: The ultra-diffuse galaxy in the NGC 5846 group (NGC 5846_UDG1) was shown to have a large number of globular cluster (GC) candidates from deep imaging as part of the VEGAS survey. Recently, Muller et al. published a velocity dispersion, based on a dozen of its GCs. Within their quoted uncertainties, the resulting dynamical mass allowed for either a dark matter free or a dark matter dominated galaxy. Here we present spectra from KCWI which reconfirms membership of the NGC 5846 group and reveals a stellar velocit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 38 publications
9
59
0
Order By: Relevance
“…The only UDG with a resolved stellar velocity dispersion profile and total halo mass fitting, Dragonfly 44 (van Dokkum et al 2019b;Wasserman et al 2019), requires a strong tangential anisotropy to fit a cuspy NFW profile to its data. Additionally, there is observational evidence against using NFW profiles to fit UDG data, coming from the comparison of dynamical mass measurements to total halo mass estimates from GC counts (Gannon et al 2020;Forbes et al 2020a). Noting the previous observational evidence against NFW profiles for UDGs that are similarly dark matter dominated and the improbably low inferred total halo masses, we suggest it likely the cuspy NFW profile poorly describes the true halo profile of UDG1137+16.…”
Section: Dynamical Masses As Halo Mass Predictorsmentioning
confidence: 69%
See 2 more Smart Citations
“…The only UDG with a resolved stellar velocity dispersion profile and total halo mass fitting, Dragonfly 44 (van Dokkum et al 2019b;Wasserman et al 2019), requires a strong tangential anisotropy to fit a cuspy NFW profile to its data. Additionally, there is observational evidence against using NFW profiles to fit UDG data, coming from the comparison of dynamical mass measurements to total halo mass estimates from GC counts (Gannon et al 2020;Forbes et al 2020a). Noting the previous observational evidence against NFW profiles for UDGs that are similarly dark matter dominated and the improbably low inferred total halo masses, we suggest it likely the cuspy NFW profile poorly describes the true halo profile of UDG1137+16.…”
Section: Dynamical Masses As Halo Mass Predictorsmentioning
confidence: 69%
“…In Figure 6 we plot our stellar velocity dispersion for UDG1137+16, along with measurements for other UDGs (van Dokkum et al 2017(van Dokkum et al , 2019bMartín-Navarro et al 2019;Danieli et al 2019;Gannon et al 2020;Forbes et al 2020a) and objects called UDGs where some debate remains as to their precise classification/properties (Chilingarian et al 2019;Collins et al 2020). Additional to this, we include UDGs from Toloba et al (2018) 3 andvan Dokkum et al (2019a) with GC kinematics under the assumption their measured GC kinematics are representative of the stellar velocity dispersion of their associated UDG (see further Forbes et al 2020a). Our UDG sample is broadly selected with no criteria related to galaxy environment.…”
Section: Formation Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…The large population of UDGs in Coma and their survival in the cluster environment suggested large total masses, 𝑀 total , despite their modest stellar masses (van Dokkum et al 2015a). Further investigations and estimations of the total mass of UDGs using stellar kinematics (van Dokkum et al 2019;Chilingarian et al 2019;Müller et al 2020;Gannon et al 2020;Forbes et al 2021), globular clusters (GCs) dynamics Toloba et al 2018), H I kinematics (Trujillo et al 2017;Leisman et al 2017;Papastergis et al 2017;Mancera Piña et al 2020;Poulain et al 2021), weak ★ E-mail: teymur.saif@gmail.com gravitational lensing (Sifón et al 2018), UDG abundance in clusters (Amorisco 2018), scaling relations (Zaritsky 2017), and X-ray observations (Lee et al 2020) found that most UDGs are dark matter dominated objects with halo masses similar to those of dwarf galaxies and dynamical mass-to-light ratios that span a wide range between a few tens to a few thousands. The most massive known UDGs have 𝑀 total ∼ 10 11 𝑀 , comparable to the most massive dwarf galaxies, such as the LMC (Erkal et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mass measurements coming from stellar, and GC velocity dispersions, for many GC-rich UDGs confirm their dark matter dominated nature (van Dokkum et al 2016;Toloba et al 2018;van Dokkum et al 2019b;Martín-Navarro et al 2019;Forbes et al 2021;Gannon et al 2020Gannon et al , 2021. When used in comparison to a total halo mass estimate coming from GC numbers they can be used to infer basic halo properties (e.g., cusp vs. core) (Toloba et al 2018;Gannon et al 2020Gannon et al , 2021Forbes et al 2021).…”
Section: Introductionmentioning
confidence: 93%